Separator in electrochemical cell stack
Patent Information
- Application Number
- JP2023142965
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
Smart Images

Figure 2025035731000001_ABST
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE An embodiment of the present invention relates to a separator for an electrochemical cell stack. [Background technology]
[0002] An electrochemical cell stack is a laminate in which cells, which are the smallest structural units of a fuel cell or an electrolysis cell, and separators are stacked in order. A fuel cell generates electricity by electrochemically reacting a fuel, such as hydrogen, with an oxidant, such as oxygen. An electrolysis cell performs electrolysis, which is the reverse reaction of the reaction in a fuel cell. For example, a water electrolysis cell electrolyzes water by an oxidation reaction at the anode, and generates hydrogen gas by a reduction reaction at the cathode.
[0003] There are electrochemical cells that use a polymer membrane as the electrolyte. For example, polymer electrolyte fuel cells (PEFCs) have a low operating temperature and are used as stationary fuel cells and fuel cells for mobile vehicles.
[0004] In fuel cells for vehicles such as automobiles, there is a demand for lightweight fuel cell stacks to reduce power consumption and extend driving distances. Because the weight of the separators accounts for the majority of the weight of a fuel cell stack, it is important to reduce the weight of the separators.
[0005] Separators in electrochemical cells using polymer membranes are generally made of carbon or metal materials. When the separator is made of carbon material, the separator is made to a thickness of about 1 mm because carbon material is a brittle material. Therefore, carbon material is not suitable as a material for reducing the weight of the separator. On the other hand, when the separator is made of metal material, the separator is made to a thickness of about 0.1 mm because metal material has high strength. By making the separator of metal material, the weight of the separator can be reduced.
[0006] Here, in electrochemical cells using polymer membranes, polymer membranes containing acids such as sulfonic acid are used. As a result, the gas flow path formed by the separator is exposed to an acidic atmosphere with a hydrogen ion concentration index (pH) of 2 to 3. Therefore, measures to prevent corrosion of the separator are important.
[0007] Carbon separators are highly resistant to acids, but are not suitable for weight reduction as described above. On the other hand, metal separators are suitable for weight reduction as described above, but are not very resistant to acids. Stainless steel (SUS) or titanium, which has high corrosion resistance, may be used as materials for metal separators. In metal separators, a corrosion-resistant film made of a precious metal such as gold or conductive carbon is provided on the surface of the separator substrate to improve corrosion resistance and reduce contact resistance with the electrodes. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2003-272649 A [Patent Document 2] Patent Publication No. 2021-26839 Summary of the Invention [Problem to be solved by the invention]
[0009] However, in conventional separators having a corrosion-resistant film on the surface of a substrate made of a metal material, defects such as pinholes and cracks may occur in the corrosion-resistant film. Even if the substrate of the separator is made of a metal material with high corrosion resistance, the substrate may come into contact with acid through the defects in the corrosion-resistant film and be corroded. Therefore, electrochemical cell stacks equipped with conventional separators have a problem of short life.
[0010] An object of the present invention is to provide a separator for an electrochemical cell stack that is lightweight and has excellent corrosion resistance. [Means for solving the problem]
[0011] The separator of the embodiment is a separator for an electrochemical cell stack in which a cell including a polymer electrolyte membrane, an anode electrode, and a cathode electrode is stacked with a separator. The separator includes a substrate made of a metal material, and a corrosion-resistant film formed on a first surface of the substrate on the anode electrode side and a second surface of the substrate on the cathode electrode side, the corrosion-resistant film being formed of crystals of a corrosion-resistant material. The arithmetic mean roughness Ra and maximum height roughness Rz of the first surface and the second surface are smaller than the grain size of the crystals. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an exploded perspective view of an electrochemical cell stack including a separator according to an embodiment. [Diagram 2] FIG. 1 is a diagram showing a partial cross section of an electrochemical cell stack including a separator according to an embodiment. [Diagram 3] FIG. 2 is a diagram illustrating a schematic cross section of a portion of a separator according to an embodiment. [Figure 4] FIG. 4 is a diagram illustrating another example of a portion of a cross section of the separator according to the embodiment. [Diagram 5] 3A to 3C are schematic diagrams for explaining the surface roughness of a substrate of a separator according to an embodiment and the configuration of a corrosion-resistant film. [Figure 6] 3A to 3C are schematic diagrams for explaining the surface roughness of a substrate of a separator according to an embodiment and the configuration of a corrosion-resistant film. [Figure 7] 3A to 3C are schematic diagrams for explaining the surface roughness of a substrate of a separator according to an embodiment and the configuration of a corrosion-resistant film. [Figure 8] 3A to 3C are schematic diagrams for explaining the surface roughness of a substrate of a separator according to an embodiment and the configuration of a corrosion-resistant film. [Figure 9] 5A to 5C are schematic diagrams for explaining other indexes of surface roughness of the substrate of the separator according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0014] (Electrochemical cell stack 1) Here, first, a configuration of an electrochemical cell stack 1 including a separator 20 will be described. Fig. 1 is an exploded perspective view of an electrochemical cell stack 1 including a separator 20 according to an embodiment. Fig. 2 is a view showing a part of a cross section of an electrochemical cell stack 1 including a separator 20 according to an embodiment.
[0015] Here, the electrochemical cell stack 1 can be used as a polymer electrolyte fuel cell stack, and also as a polymer electrolyte electrolysis cell stack.
[0016] 1 and 2, the electrochemical cell stack 1 has a structure in which a cell 10, an anode separator 30, and a cathode separator 40 are stacked as a set. The anode separator 30 and the cathode separator 40 form a pair to constitute a separator 20. The separator 20 is stacked with the cell 10 sandwiched between them.
[0017] The cell 10 includes a membrane electrode assembly (MEA) 11 and a cell outer frame 12. In the following, the membrane electrode assembly will be referred to as MEA 11. As shown in Fig. 2, the MEA 11 includes an anode electrode 13, a polymer electrolyte membrane 14, and a cathode electrode 15. The anode electrode 13, the polymer electrolyte membrane 14, and the cathode electrode 15 are configured in a flat plate shape.
[0018] An anode electrode 13 is provided on one side of the surface of a polymer electrolyte membrane 14, which is an ion exchange membrane, and a cathode electrode 15 is provided on the other side of the surface of the polymer electrolyte membrane 14. As shown in Fig. 1, a cell outer frame 12 is provided on the outer periphery of the MEA 11. The cell outer frame 12 is made of a material that is not permeable to gas.
[0019] The anode separator 30 is provided on the anode electrode 13 side. At least a portion of the anode separator 30 is in contact with the anode electrode 13. The cathode separator 40 is provided on the cathode electrode 15 side. At least a portion of the cathode separator 40 is in contact with the cathode electrode 15.
[0020] 2, the anode separator 30 and the cathode separator 40 have, for example, a corrugated shape with an isosceles trapezoidal cross section. The convex portions that form the upper base are formed alternately on the anode electrode 13 side and the cathode electrode 15 side in the direction in which the corrugated shape is formed.
[0021] Separator 20 is formed by overlapping and joining an upper base of anode separator 30 protruding toward cathode electrode 15 side and an upper base of cathode separator 40 protruding toward anode electrode 13 side.
[0022] An anode fluid flow path 31 for flowing an anode fluid is formed between the anode electrode 13 and the anode separator 30. A cathode fluid flow path 41 for flowing a cathode fluid is formed between the cathode electrode 15 and the cathode separator 40. A refrigerant flow path 21 for flowing a refrigerant is formed between the anode separator 30 and the cathode separator 40. As shown in FIG. 2, the refrigerant flow path 21 is formed by the space inside the protruding portion of the anode separator 30 that protrudes toward the anode electrode 13 side, and the space inside the protruding portion of the cathode separator 40 that protrudes toward the cathode electrode 15 side.
[0023] An end face 30a of the upper base of the anode separator 30 protruding toward the anode electrode 13 side is in contact with the anode electrode 13. An end face 40a of the upper base of the cathode separator 40 protruding toward the cathode electrode 15 side is in contact with the cathode electrode 15.
[0024] 1, anode fluid manifolds 50, 50 for supplying and discharging anode fluid, cathode fluid manifolds 51, 51 for supplying and discharging cathode fluid, and coolant manifolds 52, 52 for supplying and discharging coolant are formed in the cell outer frame 12, the anode separator 30, and the cathode separator 40. Note that, of each manifold, one is a manifold for supplying a fluid, and the other is a manifold for discharging the fluid.
[0025] Each flow path of the anode fluid, cathode fluid, and refrigerant is sealed with a sealant 60 to prevent leakage of the fluid to the outside. As shown in Fig. 1, the sealant 60 for the cathode fluid is formed, for example, on the surface of the cathode separator 40 facing the cathode electrode 15. The sealant 60 for the refrigerant is formed, for example, on the surface of the anode separator 30 facing the cathode separator 40. The sealant 60 for the anode fluid is formed, for example, on the surface of the anode separator 30 facing the anode electrode 13.
[0026] Although an example in which the sealing material 60 is formed on the anode separator 30 and the cathode separator 40 has been shown here, the sealing material 60 may be formed on the cell 10. Also, a gasket may be provided as the sealing material 60 between each surface to be sealed.
[0027] 1, the anode fluid flow path 31, the cathode fluid flow path 41, and the coolant flow path 21 are configured in a serpentine structure having multiple bends, but the configuration is not limited to this. Each flow path may be configured in a straight line structure without bends.
[0028] When the electrochemical cell stack 1 is used as a polymer electrolyte fuel cell stack, hydrogen is mainly used as the anode fluid, and oxygen or air is mainly used as the cathode fluid. Note that substances other than those mentioned above may be used as the anode fluid and the cathode fluid.
[0029] For example, when hydrogen is used as the anode fluid and oxygen is used as the cathode fluid, hydrogen supplied to one anode fluid manifold 50 is introduced into the anode fluid channel 31. Oxygen supplied to one cathode fluid manifold 51 is introduced into the cathode fluid channel 41. Hydrogen and oxygen are used as reactants in the chemical reaction accompanying power generation in the cell 10.
[0030] Hydrogen that is not used as a reactant is discharged to the outside from the other anode fluid manifold 50. Moreover, oxygen that is not used as a reactant is discharged to the outside from the other cathode fluid manifold 51 together with the products of the chemical reaction.
[0031] When the electrochemical cell stack 1 is used as a solid polymer electrolytic cell stack, the solid polymer electrolytic cell stack is used for carbon dioxide electrolysis, water electrolysis, etc. When used for carbon dioxide electrolysis, water is used as the anode fluid, and carbon dioxide is used as the cathode fluid. When used for water electrolysis, water is used as the anode fluid. A predetermined voltage is applied between the anode electrode 13 and the cathode electrode 15 from the outside.
[0032] When used for carbon dioxide electrolysis, water supplied to one of the anode fluid manifolds 50 is introduced into the anode fluid flow channel 31. Carbon dioxide supplied to one of the cathode fluid manifolds 51 is introduced into the cathode fluid flow channel 41. The water and carbon dioxide are used as reactants in the chemical reaction in the cell 10.
[0033] Water that is not used as a reactant is discharged to the outside together with the products of the chemical reaction from the other anode fluid manifold 50. Carbon dioxide that is not used as a reactant is discharged to the outside together with the products of the chemical reaction from the other cathode fluid manifold 51.
[0034] When used for water electrolysis, water supplied to one of the anode fluid manifolds 50 is introduced into the anode fluid flow channel 31. The water is used as a reactant in the chemical reaction in the cell 10.
[0035] Water that is not used as a reactant is discharged to the outside together with the products of the chemical reaction from the other anode fluid manifold 50. On the cathode side, the products of the chemical reaction are discharged to the outside from the other cathode fluid manifold 51.
[0036] Here, when the electrochemical cell stack 1 is used as a polymer electrolyte fuel cell stack or a polymer electrolyte electrolysis cell stack, the coolant supplied to one of the coolant manifolds 52 is introduced into the coolant flow path 21. The coolant that has cooled the MEA 11 is discharged to the outside from the other coolant manifold 52. For example, water is used as the coolant. Note that a substance other than water may be used as the coolant.
[0037] (Separator 20) Next, the configuration of the separator 20 will be described in detail.
[0038] 3 is a schematic diagram showing a part of a cross section of separator 20 according to an embodiment. As shown in FIG. 3, anode separator 30 and cathode separator 40 constituting separator 20 include a substrate 80 and a corrosion-resistant film 90.
[0039] The substrate 80 is formed of a metal thin plate such as stainless steel (SUS), titanium, aluminum, an aluminum alloy, magnesium, a magnesium alloy, etc. Specifically, the substrate 80 is formed of one material selected from these materials.
[0040] The thickness of the base material 80 is, for example, about 0.1 mm. Here, by forming the base material 80 from aluminum, an aluminum alloy, magnesium, or a magnesium alloy, it is possible to achieve further weight reduction.
[0041] The base material 80 is formed into, for example, the above-mentioned isosceles trapezoidal corrugated shape by, for example, pressing the above-mentioned metal thin plate. The pressing may be performed before or after the corrosion-resistant film 90 is formed.
[0042] The corrosion-resistant film 90 prevents the substrate 80 from being corroded by exposure to an acidic atmosphere. The corrosion-resistant film 90 is formed on at least one surface 80a of the substrate 80. In the anode separator 30, the corrosion-resistant film 90 is formed at least on the surface of the substrate 80 on the anode electrode 13 side. The surface of the substrate 80 on the anode electrode 13 side in the anode separator 30 means the entire surface of the substrate 80 facing the anode electrode 13. In the cathode separator 40, the corrosion-resistant film 90 is formed at least on the surface of the substrate 80 on the cathode electrode 15 side. The surface of the substrate 80 on the cathode electrode 15 side in the cathode separator 40 means the entire surface of the substrate 80 facing the cathode electrode 15.
[0043] The corrosion-resistant film 90 is formed of a material that is corrosion-resistant and conductive. The corrosion-resistant film 90 is formed of, for example, Ti, Ta, TiN, TaN, TiC, TaC, TiCN, TaCN, conductive carbon, etc. Specifically, the corrosion-resistant film 90 is formed of a plurality of crystals of one material selected from these materials.
[0044] The corrosion-resistant film 90 is formed by a film forming method such as chemical vapor deposition (CVD), atomic layer deposition (ALD), or physical vapor deposition (PVD) such as sputtering. By using these film forming methods, a film with few defects and good embedding properties can be formed. In addition, by using these film forming methods, a film with good covering properties can be formed. Furthermore, by using these film forming methods, a film with a uniform thickness can be formed on the surface of the separator 20 having an isosceles trapezoidal wave shape.
[0045] Here, when the base material 80 is made of magnesium or a magnesium alloy, these materials are quickly oxidized in the atmosphere to form an oxide film. Therefore, in order to suppress the formation of an oxide film on the surface of the base material 80, it is preferable to form the corrosion-resistant film 90 immediately after adjusting the surface roughness of the surface 80a of the base material 80, or to form the corrosion-resistant film 90 using the base material 80 that has been controlled in an atmosphere that does not contain oxygen.
[0046] An oxide film may be formed on the surface of the base material 80 to function as a passivation film for improving corrosion resistance. If the passivation film is thick, depending on the material, the insulating properties may become high and current may not flow easily. Therefore, the oxide film (passivation film) is formed to an appropriate thickness, taking into account corrosion resistance and insulating properties. For example, when the base material 80 is aluminum, the thickness of the oxide film (aluminum oxide) is preferably 1 nm to 10 nm.
[0047] Here, Fig. 4 is a diagram showing a schematic view of another example of a part of a cross section of the separator 20 of the embodiment. As shown in Fig. 4, in a portion where the anode separator 30 contacts the anode electrode 13, a conductive film 100 may be formed on the surface of the corrosion-resistant film 90 on the anode electrode 13 side. Also, in a portion where the cathode separator 40 contacts the cathode electrode 15, a conductive film 100 may be formed on the surface of the corrosion-resistant film 90 on the cathode electrode 15 side.
[0048] The conductive film 100 may be formed at least on the surface of the corrosion-resistant film 90 that contacts the anode electrode 13 and at least on the surface of the corrosion-resistant film 90 that contacts the cathode electrode 15. The portion of the anode separator 30 that contacts the anode electrode 13 is the end face 30a of the upper base of the anode separator 30 facing the anode electrode 13, and the portion of the cathode separator 40 that contacts the cathode electrode 15 is the end face 40a of the upper base of the cathode separator 40 facing the cathode electrode 15 (see FIG. 2).
[0049] The provision of the conductive film 100 can reduce the contact resistance at the contact portion between the anode electrode 13 or the cathode electrode 15 and the separator 20. It is preferable to provide the conductive film 100 when the corrosion-resistant film 90 is formed of Ti, Ta, TiN, TaN, TiC, TaC, TiCN, or TaCN.
[0050] The conductive film 100 is formed of a material having excellent conductivity, mainly composed of carbon. The conductive film 100 is formed of, for example, conductive carbon. The conductive film 100 is formed by, for example, chemical vapor deposition (CVD) or physical vapor deposition (PVD) such as sputtering.
[0051] The contact resistivity of each separator and electrode is set to 10 mΩ cm in accordance with the guidelines of the U.S. Department of Energy. 2 It is preferable that the contact resistivity is equal to or less than 100%. Note that the contact resistivity shown here is a value measured by overlapping each separator and each electrode with a four-terminal method under a load of 1 MPa.
[0052] Next, the surface roughness of the surface 80a of the base material 80 on which the corrosion-resistant film 90 is formed and the corrosion-resistant film 90 will be described.
[0053] 5 to 8 are schematic diagrams for explaining the surface roughness of the substrate 80 and the configuration of the corrosion-resistant film 90 of the separator 20 according to the embodiment.
[0054] The surface roughness of the surface 80a of the substrate 80 is adjusted by surface polishing or the like. The adjustment of the surface roughness is performed, for example, by sandpaper, mechanical polishing, or the like. The surface roughness is indicated by the arithmetic mean roughness (Ra) (JIS B 0601:2013) and the maximum height roughness (Rz) (JIS B 0601:2013). Generally, the maximum height roughness (Rz) is greater than the arithmetic mean roughness (Ra).
[0055] The arithmetic mean roughness (Ra) of the surface 80a of the substrate 80 is preferably 0.01 μm or less. The arithmetic mean roughness (Ra) of the surface 80a is more preferably 0.005 μm or less. The arithmetic mean roughness (Ra) of the surface 80a is further preferably 0.002 μm or less.
[0056] Moreover, the maximum height roughness (Rz) of the surface 80a of the base material 80 is preferably 0.1 μm or less. The maximum height roughness (Rz) of the surface 80a is more preferably 0.05 μm or less. The maximum height roughness (Rz) of the surface 80a is further preferably 0.02 μm or less.
[0057] Here, the corrosion-resistant film 90 is formed of a plurality of crystals made of a corrosion-resistant material, as shown in Figs. 5 to 8. Figs. 5 and 6 show a configuration in which the corrosion-resistant film 90 is composed of spherical crystals 91. Figs. 7 and 8 show a configuration in which the corrosion-resistant film 90 is composed of columnar crystals 92. Figs. 5 and 7 show a configuration in which the surface roughness on the surface 80a is small. Figs. 5 and 7 show a case in which the maximum height roughness (Rz) is smaller than the average grain size of the crystals. Figs. 6 and 8 show a configuration in which the surface roughness on the surface 80a is large. Figs. 6 and 8 show a case in which the maximum height roughness (Rz) is larger than the average grain size of the crystals.
[0058] Here, the average grain size of the spherical crystals 91 means the arithmetic mean value of the grain size of each of the spherical crystals 91. The average grain size of the columnar crystals 92 means the arithmetic mean value of the diameter of each of the columnar crystals 92 in a cross section perpendicular to the growth direction of the columnar crystals 92. The grain size Φ of each crystal is measured using a scanning electron microscope (SEM).
[0059] As shown in Figures 5 and 7, when the surface roughness is small, the unevenness of the surface of the corrosion-resistant film 90 is also small. On the other hand, as shown in Figures 6 and 8, when the surface roughness is large, the unevenness of the surface of the corrosion-resistant film 90 is also large. In other words, the shape of the surface of the corrosion-resistant film 90 is affected by the shape of the surface 80a of the substrate 80. Furthermore, defects such as cavities and cracks in the corrosion-resistant film 90 are more likely to occur when the surface of the corrosion-resistant film 90 has large unevenness than when the surface of the corrosion-resistant film 90 has small unevenness.
[0060] The crystals constituting the corrosion-resistant film 90 grow upward from the surface 80a of the substrate 80. Specifically, the crystals constituting the corrosion-resistant film 90 grow in a direction almost perpendicular to the surface 80a. Therefore, on the surface 80a, the crystals growing from the inclined surface inclined to the horizontal direction interfere with the crystals growing from the non-inclined surface 80a, and the growth is inhibited. As a result, the corrosion-resistant film 90 composed of the crystals grown under such conditions is prone to defects such as cavities and cracks. The surface 80a of the substrate 80 provided with the corrosion-resistant film 90 having defects is corroded by exposure to an acidic substance, i.e., an acidic atmosphere.
[0061] Moreover, the arithmetic mean roughness (Ra) and maximum height roughness (Rz) on the surface 80a of the base material 80 are preferably smaller than the average grain size of the crystals constituting the corrosion-resistant film 90. In other words, the average grain size of the crystals constituting the corrosion-resistant film 90 is preferably larger than the arithmetic mean roughness (Ra) and maximum height roughness (Rz) on the surface 80a. When the grain size of the crystals is larger than the surface roughness (Ra, Rz) on the surface 80a, the crystals tend to grow in the vertical direction from the surface 80a of the base material 80. This suppresses the occurrence of defects such as cavities and cracks in the corrosion-resistant film 90.
[0062] Here, the thicker the corrosion-resistant film 90, the higher the corrosion resistance. Therefore, it is preferable that the thickness of the corrosion-resistant film 90 is at least thicker than the maximum height roughness (Rz) and the arithmetic mean roughness (Ra). The thickness of the corrosion-resistant film 90 is the distance from the surface 80a of the substrate 80 to the surface of the corrosion-resistant film 90 in the z-axis direction in Figs. 5 to 8.
[0063] The thickness of the corrosion-resistant film 90 is preferably such that the irregularities on the surface 80a of the substrate 80 are completely covered by the corrosion-resistant film 90. The thickness of the corrosion-resistant film 90 is preferably set to, for example, at least twice the maximum height roughness (Rz). For example, when the corrosion-resistant film 90 as shown in Fig. 5 is composed of spherical crystals 91, the corrosion-resistant film 90 is obtained in which the spherical crystals 91 are stacked in multiple stages in the growth direction.
[0064] In order to reduce defects in the corrosion-resistant film 90, the range of variation in the thickness of the corrosion-resistant film 90 is also an important parameter. Therefore, the range of variation in the thickness of the corrosion-resistant film 90 is preferably within a range of ±20% of the average thickness of the corrosion-resistant film 90, and more preferably within a range of ±10% of the average thickness of the corrosion-resistant film 90. In other words, the thickness of the corrosion-resistant film 90 formed on the surface 80a of the base material 80 is preferably 120% or less and 80% or more of the average thickness of the corrosion-resistant film 90, and more preferably 110% or less and 90% or more of the average thickness of the corrosion-resistant film 90. The average thickness here is the arithmetic mean value of the thickness at a plurality of points in a predetermined range where the corrosion-resistant film 90 is formed.
[0065] Next, other indexes of the surface roughness of the surface 80a of the base material 80 will be described.
[0066] In the above-mentioned surface roughness, the maximum height difference of the surface irregularities within a certain range is described as the maximum height roughness (Rz). Here, an index of surface roughness focusing on each irregularity of the surface 80a of the substrate 80 will be described.
[0067] FIG. 9 is a schematic diagram for explaining another index of the surface roughness of the substrate 80 of the separator 20 according to the embodiment.
[0068] As shown in Fig. 9, the surface 80a of the substrate 80 has a surface roughness shape with an uneven structure in which peaks 110 and valleys 120 are repeatedly and continuously formed. The peaks 110 are parts that are convex upward in Fig. 9, and the valleys 120 are parts that are convex downward in Fig. 9. In other words, the peaks 110 form convex parts, and the valleys 120 form concave parts.
[0069] Here, zi denotes the vertical distance between the top 110a of the peak 110 and the bottom 120a of the valley 120 adjacent to this peak 110. Also, xi denotes the horizontal distance between the top 110a of the peak 110 and the bottom 120a of the valley 120 adjacent to this peak 110. In FIG. 9, the top 110a is the portion of each peak 110 that protrudes most upward. The bottom 120a is the portion of each valley 120 that is recessed most downward.
[0070] In the subscript i of x and z shown in FIG. 9, the tens digit is a number indicating each peak 110 and each valley 120. The ones digit of the subscript i is a number indicating the horizontal distance and vertical distance of one side and the horizontal distance and vertical distance of the other side in each peak 110 and each valley 120. For example, in FIG. 9, the tens digit of the subscript i of the third peak 110 is "3". In the third peak 110, the ones digit of the subscript i indicating the horizontal distance and vertical distance of one side is "1", and the ones digit of the subscript i indicating the horizontal distance and vertical distance of the other side is "2".
[0071] Here, as another index of surface roughness, the aspect ratio ARi is defined as the ratio (zi / xi) of the horizontal distance xi to the vertical distance zi between the top 110a of the peak 110 and the bottom 120a of the valley 120 adjacent to this peak 110. The horizontal distance xi and the vertical distance zi are measured using an electron microscope or the like.
[0072] The larger the value of the aspect ratio ARi, the steeper the slope of the surface 80a, and the smaller the value of the aspect ratio ARi, the gentler the slope of the surface 80a.
[0073] 9, the angle of the bend in the peak 110 or the valley 120 is indicated by θj. The angle θj of the bend in the peak 110 is the angle of expansion downward from the apex 110a of the peak 110. The angle θj of the bend in the valley 120 is the angle of expansion upward from the bottom 120a of the valley 120.
[0074] In addition, the tens digit of the subscript j of θ shown in FIG. 9 is a number indicating each peak 110 and each valley 120. In addition, the ones digit of the subscript j is a number indicating whether it is a peak 110 or a valley 120, with "1" being used for the peak 110 and "2" being used for the valley 120. For example, in FIG. 9, the tens digit of the subscript j for the third peak 110 is "3." In addition, the ones digit of the subscript j for the third peak 110 is "1."
[0075] Here, the angle θj at each peak 110 is defined as follows: Tangents K and L are drawn on the left and right surfaces 80a at an arbitrarily determined position in the negative direction of the z axis (vertically downward in FIG. 9) from the peak 110a of the peak 110. The angle θj at each peak 110 is the angle on the peak 110a side between the tangent K and the tangent L, with the intersection O of these tangents K and L as the center.
[0076] Similarly, the angle θj at each valley 120 is defined as follows: Tangents M and N are drawn on the left and right surfaces 80a at an arbitrarily determined position in the positive direction of the z axis (vertically upward in FIG. 9) from the bottom 120a of the valley 120. The angle θj at each peak 110 is the angle on the bottom 120a side between the tangent M and the tangent N with the intersection O of these tangents M and N as the center.
[0077] The smaller the angle θj, the steeper the slope of the surface 80a, and the larger the angle θj, the gentler the slope of the surface 80a.
[0078] Here, in order to suppress the occurrence of defects such as cavities and cracks in the corrosion-resistant film 90 formed on the surface 80a of the base material 80, it is preferable that crystals are densely formed on the surface 80a. For example, if the slope of the surface 80a is steep and the valleys 120 are deep, it is difficult to embed crystals in the valleys 120. In order to properly embed crystals in the valleys 120, a configuration with a small aspect ratio ARi is preferable. Also, in order to properly embed crystals in the valleys 120, a configuration with a large angle θj is preferable.
[0079] Therefore, the aspect ratio ARi is preferably 1.0 or less, and more preferably 0.5 or less, and the angle θj is preferably 120 degrees or more, and more preferably 150 degrees or more.
[0080] Here, the above-mentioned setting of the surface roughness (Ra, Rz) of surface 80a of substrate 80 and the configuration of corrosion-resistant film 90 are applied to the surface of substrate 80 exposed to an acidic atmosphere in anode separator 30 and cathode separator 40. Specifically, the above-mentioned setting of the surface roughness (Ra, Rz) and the configuration of corrosion-resistant film 90 are applied to at least the surface of substrate 80 on the anode electrode 13 side in anode separator 30, and are applied to at least the surface of substrate 80 on the cathode electrode 15 side in cathode separator 40.
[0081] Here, it is sufficient that the surface of the substrate 80 that is not exposed to the acidic atmosphere, i.e., the surface of the substrate 80 that forms the refrigerant flow path 21, does not corrode in an environment exposed to the refrigerant. That is, the setting of the surface roughness (Ra, Rz) of the surface of the substrate 80 that is not exposed to the acidic atmosphere and the configuration of the corrosion-resistant film 90 do not have to apply the setting of the surface roughness (Ra, Rz) of the surface 80a of the substrate 80 and the configuration of the corrosion-resistant film 90 described above. For example, the setting of the surface roughness (Ra, Rz) of the substrate 80 that is not exposed to the acidic atmosphere and the configuration of the corrosion-resistant film 90 may be based on conventional general specifications.
[0082] (Corrosion resistance evaluation) Here, the corrosion resistance was evaluated by evaluating sulfuric acid resistance. Table 1 shows the specifications of the samples evaluated and the evaluation results. Samples 1 and 2 in Table 1 are examples of the present embodiment, and samples 3 and 4 are comparative examples.
[0083] [Table 1]
[0084] A 0.1 mm-thick magnesium alloy thin plate was used as the substrate for the separator. One surface of the substrate was mechanically polished using a slurry, and the arithmetic mean roughness (Ra) and maximum height roughness (Rz) of one surface of each sample were measured as shown in Table 1. The arithmetic mean roughness (Ra) and maximum height roughness (Rz) were measured using a laser interference surface roughness meter.
[0085] Next, a corrosion-resistant film made of titanium (Ti) or tantalum (Ta) was formed with a thickness of 300 nm on the polished surface of the substrate by sputtering. Note that the substrate before the corrosion-resistant film was formed was kept in an oxygen-free atmosphere.
[0086] The corrosion-resistant film was observed with a scanning electron microscope, and the grain size of each crystal constituting the corrosion-resistant film was measured. The arithmetic mean of the grain sizes of each measured crystal was then calculated as the average grain size. The calculated average grain size is shown in Table 1.
[0087] In the evaluation of sulfuric acid resistance, a 5% aqueous sulfuric acid solution was dropped onto the corrosion-resistant film with a dropper, and the time until foaming occurred was measured. Since foaming occurs when the magnesium of the substrate reacts with sulfuric acid, the shorter the time until foaming occurs, the worse the sulfuric acid resistance.
[0088] As shown in Table 1, Samples 1 and 2, which have small surface roughness (Ra, Rz), have higher sulfuric acid resistance than Samples 3 and 4, which have large surface roughness. Also, Samples 1 and 2, which have surface roughness (Ra, Rz) smaller than the average grain size of the crystals, have higher sulfuric acid resistance than Samples 3 and 4, which have surface roughness (Ra, Rz) larger than the average grain size of the crystals.
[0089] From these results, it is considered that in Samples 3 and 4, which have large surface roughness, the crystals growing from the inclined surface inclined to the horizontal direction on the substrate surface interfere with the crystals growing from the non-inclined surface, inhibiting their growth. As a result, defects such as cavities and cracks occur in the corrosion-resistant film of Samples 3 and 4, and it is considered that the sulfuric acid aqueous solution penetrates through the defects and reaches the substrate. For this reason, Samples 3 and 4 have poor sulfuric acid resistance.
[0090] On the other hand, in Sample 1 and Sample 2, which have small surface roughness, it is believed that interference between growing crystals is suppressed. As a result, it is believed that the occurrence of defects such as cavities and cracks in the corrosion-resistant film is suppressed in Sample 1 and Sample 2, and that contact of the substrate with the sulfuric acid aqueous solution is suppressed. Therefore, Sample 1 and Sample 2 have excellent sulfuric acid resistance.
[0091] As described above, according to the separator 20 of the present embodiment, by setting the arithmetic mean roughness (Ra) and maximum height roughness (Rz) of the surface 80a of the substrate 80 of the separator 20 facing the anode electrode 13 and the surface 80a of the substrate 80 of the separator 20 facing the cathode electrode 15 within the above-mentioned ranges, a corrosion-resistant film with reduced defects can be formed on the surface 80a. This prevents the surface 80a of the substrate 80 from being exposed to acid. Therefore, a separator 20 with excellent corrosion resistance can be obtained, and an electrochemical cell stack 1 with a long life can be provided.
[0092] Furthermore, by providing the configuration of the separator 20 of this embodiment, the separator 20 itself can be made of a thin metal material, and therefore the weight of the electrochemical cell stack 1 can be reduced.
[0093] Furthermore, as described above, by setting the aspect ratio ARi and the angle θj of the bends in the peaks 110 and valleys 120, which are other indexes of surface roughness, within the above-mentioned predetermined ranges, a corrosion-resistant film with reduced defects can be formed on the surface 80a of the substrate 80 of the separator 20. This prevents the surface 80a of the substrate 80 from being exposed to acid. Therefore, a separator 20 with excellent corrosion resistance can be obtained, and an electrochemical cell stack 1 with a long life can be provided.
[0094] According to the embodiment described above, it is possible to provide a separator for an electrochemical cell stack that is lightweight and has excellent corrosion resistance.
[0095] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0096] 1...electrochemical cell stack, 10...cell, 11...membrane electrode assembly (MEA), 12...cell outer frame, 13...anode electrode, 14...polymer electrolyte membrane, 15...cathode electrode, 20...separator, 21...coolant flow path, 30...anode separator, 30a, 40a...end surface, 31...anode fluid flow path, 40...cathode separator, 41...cathode fluid flow path, 50...anode fluid manifold, 51...cathode fluid manifold, 52...coolant manifold, 60...sealing material, 80...substrate, 80a...surface, 90...corrosion-resistant film, 91...spherical crystals, 92...columnar crystals, 100...conductive film, 110...ridge portion, 110a...top portion, 120...valley portion, 120a...bottom portion.
Claims
1. A separator for an electrochemical cell stack in which a cell including a polymer electrolyte membrane, an anode electrode, and a cathode electrode is stacked with a separator, A substrate formed of a metal material; a corrosion-resistant film formed on a first surface of the substrate facing the anode electrode and a second surface of the substrate facing the cathode electrode, the corrosion-resistant film being made of crystals of a corrosion-resistant material; Equipped with A separator for an electrochemical cell stack, wherein the arithmetic mean roughness Ra and the maximum height roughness Rz of the first surface and the second surface are smaller than the grain size of the crystals.
2. 2. The separator for an electrochemical cell stack according to claim 1, wherein the crystals are spherical crystals, and the grain size is an average grain size of the crystals.
3. 2. The separator for an electrochemical cell stack according to claim 1, wherein the crystals are columnar crystals, and the grain size is an average value of diameters in a cross section perpendicular to the growth direction of the crystals.
4. 2. The separator for an electrochemical cell stack according to claim 1, wherein the arithmetic mean roughness Ra of the first surface and the second surface is 0.01 μm or less.
5. 2. The separator for an electrochemical cell stack according to claim 1, wherein the maximum height roughness Rz of the first surface and the second surface is 0.1 μm or less.
6. the first surface and the second surface have a surface roughness profile in which upwardly convex peaks and downwardly convex valleys are repeatedly and continuously formed, 2. The separator for an electrochemical cell stack according to claim 1, characterized in that an aspect ratio ARi, which is the ratio (zi / xi) of the horizontal distance xi to the vertical distance zi at the top of the ridge portion and the bottom of the valley portion adjacent to the ridge portion, is 1.0 or less.
7. the first surface and the second surface have a surface roughness profile in which upwardly convex peaks and downwardly convex valleys are repeatedly and continuously formed, 2. The separator for an electrochemical cell stack according to claim 1, wherein the downward spreading angle from the top of said ridges and the upward spreading angle from the bottom of said valleys are 120 degrees or more.
8. 2. The separator for an electrochemical cell stack according to claim 1, wherein the range of variation in thickness of the corrosion-resistant film is within a range of ±20% of the average thickness of the corrosion-resistant film.
9. 2. The separator for an electrochemical cell stack according to claim 1, wherein the corrosion-resistant film is made of a material having electrical conductivity.
10. 2. The separator of an electrochemical cell stack according to claim 1, wherein the corrosion-resistant film is formed of one material selected from the group consisting of Ti, Ta, TiN, TaN, TiC, TaC, TiCN, TaCN and conductive carbon.
11. 2. The separator for an electrochemical cell stack according to claim 1, further comprising a passivation film formed between said substrate and said corrosion-resistant film.
12. In the corrosion-resistant film formed on the first surface and the second surface, 2. The separator of an electrochemical cell stack according to claim 1, characterized in that a conductive film mainly composed of carbon is formed on at least a surface of the corrosion-resistant film in contact with the anode electrode, and on at least a surface of the corrosion-resistant film in contact with the cathode electrode.
13. the separator is configured by laminating an anode separator provided on the anode electrode side and a cathode separator provided on the cathode electrode side, 2. The separator for an electrochemical cell stack according to claim 1, wherein a coolant flow passage for flowing a coolant is formed between said anode separator and said cathode separator.
14. 2. The separator of claim 1, wherein the substrate is made of one material selected from the group consisting of stainless steel, titanium, aluminum, an aluminum alloy, magnesium, and a magnesium alloy.
Citation Information
Patent Citations
Manufacturing method of metal separator for fuel cell
JP2003272649A
Manufacturing method of separator for fuel cell
JP2021026839A